Effect of catalyst in the synthesis of orange peel biomass derived CNTs - Sadika Farsana; Moh’d Rezeq; Sufian Abedrabbo; Dirar Homouz; Shashikant P. Patole; Jamal Hassan (Scientific Reports)
Abstract Carbon nanomaterials, particularly carbon nanotubes (CNTs), have attracted considerable research attention due to their exceptional properties, including high electrical conductivity, stability, and surface area. These properties make CNTs suitable for diverse applications in energy, environment, and biomedicine. However, the conventional methods of synthesizing CNTs are energy-intensive, expensive, and environmentally harmful. Moreover, the reliance on traditional non-renewable precursor graphite is another challenge. To address these issues and promote sustainability research, using biomass as a renewable precursor for synthesizing CNTs offers a promising alternative to traditional approaches. This study presents a novel synthesis method for producing multi-walled CNT with an average diameter of 10 nm. The process involves a two-stage pyrolysis of dried orange peel catalyzed by ferrocene and purification with concentrated sulfuric acid. Various characterization techniques, including UV-Vis, FTIR, XRD, Raman Spectroscopy, SEM-EDS, and TEM, were employed to analyze the synthesized carbon nanomaterial. Results indicate that the physiochemical properties of CNTs were influenced by the catalyst quantity applied during pyrolysis. Specifically, the carbon material derived from orange peel, synthesized at 800℃ with a higher catalyst concentration, yielded well-aligned CNTs ranging in size from 8.0 to 15 nm, exhibiting minimal structural defects. This study reveals the feasibility, cost-effectiveness, and environmental sustainability of synthesizing biomass-derived CNTs.